Ageing effects on humoral immune responses in chronic periodontitis. (26th April 2018) - Ebersole, Jeffrey L.; Al‐Sabbagh, Mohanad; Gonzalez, Octavio A.; Dawson, Dolph R.
Abstract: Periodontal disease is a dominant global bacterial infection that increases with ageing. Aim: This report focuses on host adaptive immune responses in periodontitis. While experimental models and humans diagnosed with periodontitis demonstrate an antigenic specificity for particular oral bacteria, we have a limited understanding of (i) how ageing affects the adaptive immune responses to these bacteria that chronically colonize the oral cavity for decades prior to disease expression and (ii) how the magnitude and specificity of the response interface with pathogens that emerge within the bacterial ecology during exacerbations of disease. Materials and Methods: Serum antibody levels to a group of pathogenic and commensal oral bacteria were measured in a population of individuals from 21 to 74 years of age, stratified based on clinical status of the periodontium, smoking and sex. Results: Clinical parameters were not significantly different within health, gingivitis or periodontitis groups related to age. Antibody to oral pathogens and commensals was similar in different age groups in each of the clinical categories, with no age correlation noted in the periodontitis patients. Conclusions: The adaptive immune responses to oral bacteria that chronically colonize the oral cavity appear generally unaffected by age, but clearly are linked to the extent of disease.